Recovery under sail: Rehabilitation clients' experience of a sail training voyage. (2nd September 2016) - White, Robert; Abraham, Charles; Smith, Jane R.; White, Mathew; Staiger, Petra K.
Abstract: Sail training refers to sea voyages designed to foster personal and social change. Such training has mainly involved young people but may have the potential to benefit adults who are recovering from drug and alcohol addiction. During the voyage described here clients in drug rehabilitation centres across the UK were given the opportunity to participate in a 5-day sail training voyage. Pre- and post-voyage interviews were conducted with 11 clients to explore their experiences of being selected and participating in this voyage. Clients enjoyed the experience and found it to be beneficial, promoting self-insight, new life plans and social skills development. Living in an unfamiliar, potentially dangerous and inescapable environment necessitating close proximity to others and teamwork under the supervision of expert authority figures generated bonding with and caring for others; as well as the development of new competencies and greater self-confidence. The findings suggest that sail training can be beneficial to clients in recovery from addiction and highlight key features that may optimise effectiveness.